Cellular lethal damage of 64Cu incorporated in mammalian genome evaluated with Monte Carlo methods - Carrasco-Hernandez, Jhonatan; Ramos-Méndez, José; Padilla-Rodal, Elizabeth; Avila-Rodriguez, Miguel A. (Frontiers in Medicine, 2023)
Purpose: The aim of this study is to quantify the DNA damage and radiotherapeutic potential of the promising AE radionuclide copper-64 ( 64 Cu) incorporated into the DNA of mammalian cells using Monte Carlo track-structure simulations. Methods: A mammalian cell nucleus model with a diameter of 9.3 µm available in TOPAS-nBio was used. The cellular nucleus was irradiated with monoenergetic electrons and radiation emissions from several radionuclides including 111 In, 125 I, 123 I, 99m Tc in addition to 64 Cu. For monoenergetic electrons, isotropic point sources randomly distributed within the nucleus were modeled. The radionuclides were incorporated in randomly chosen DNA base pairs at two positions near to the central axis of the double-helix DNA model at 1) 0.25 nm off the central axis and 2) at the periphery of the DNA (1.15 nm off the central axis). The DNA Double Strand Breaks (DSB) yield per decay from direct and indirect actions were quantified. The DSB yields per decay incorporated in DNA for 64 Cu are first reported in this work. The therapeutic effect of 64 Cu (activity that led 37% cell survival after two cell divisions) was determined in terms of the number of atoms incorporated into the nucleus that would lead to the same DSBs that 100 decays of 125 I. Results: The behavior of DSBs as a function of the energy for monoenergetic electrons was consistent with published data, the DSBs increased with the energy until it reached a maximum value near 500 eV followed by a continuous decrement. For 64 Cu, when incorporated in the genome at evaluated positions 1) and 2), the DSB were 0.171 ± 0.003 and 0.190 ± 0.003 DSB/decay, respectively. The number of initial atoms incorporated into the genome (per cell) for 64 Cu that would cause a therapeutic effect was estimated as 3107 ± 28, that corresponds to an initial activity of 47.1 ± 0.4 × 10 -3 Bq. Conclusion: Our results showed that TRT with 64 Cu has comparable therapeutic effects in cells as that of TRT with radionuclides currently used in clinical practice.